Construção da identidade profissional docente de estagiários em educação física - Pires, Veruska (2019)
The aim of the study was to analyze the professional identity construction of trainee students in Physical Education, considering the categories established by Dubar (1997) This was based on the experiences lived before the period of undergraduate, during the period of undergraduate, and during the curricular internships. The participants were 59 students from two undergraduate majors in Physical Education of Florianópolis. Evidence has shown that the time prior to the undergraduate period is loaded with biographical identity processes from inherited identity. During the undergraduate period, the inherited identity loses its space to a targeted identity, but with marks of the virtual social identity. The few essays on and in teaching done in the stages guarantee the configuration of a required identity, based on the acts of attribution and belonging. We conclude that the individual teacher identity is marked by the crises of identity, originated in a time of discovery and calls for a collective teaching identity to be realized in a real social identity.